2003
DOI: 10.1007/s00253-002-1190-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of factors impeding the production of a single-chain antibody fragment in Escherichia coli by comparing in vivo and in vitro expression

Abstract: In order to produce the atrazine-specific scFv K411B, it was expressed in either the cytoplasm or the periplasm of Escherichia coli BL21(DE3). For periplasmic production, the scFv was N-terminally fused to the pelB leader, whereas the unfused variant resulted in cytoplasmic expression. The extent of protein accumulation differed significantly: The expression level of the scFv with leader was 2.3 times higher than that of the protein without leader. To further investigate this, the respective translation profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
1
7
1
Order By: Relevance
“…Out of all the recombinant systems studied, E. coli/pCS22 host was found to be optimum because of its efficient protein expression, folding and secretion to the periplasmic space. The total protein concentration in the periplasmic fraction (96 mg/L) was higher than in previous published reports on periplasmic protein expression using pelB leader sequence [23,24]. This variation in total recombinant protein concentration may be due to variation in vector characteristics, choice and source of gene or choice of host organism.…”
Section: Cell Growth and A-amylase Expression In Bioreactorcontrasting
confidence: 80%
“…Out of all the recombinant systems studied, E. coli/pCS22 host was found to be optimum because of its efficient protein expression, folding and secretion to the periplasmic space. The total protein concentration in the periplasmic fraction (96 mg/L) was higher than in previous published reports on periplasmic protein expression using pelB leader sequence [23,24]. This variation in total recombinant protein concentration may be due to variation in vector characteristics, choice and source of gene or choice of host organism.…”
Section: Cell Growth and A-amylase Expression In Bioreactorcontrasting
confidence: 80%
“…Therefore, in E. coli it is usually desirable to express scFvs as fusion proteins targeted for translocation to the oxidative periplasm to obtain functional products (3,26). Various vector systems for recombinant scFv expression in E. coli have been reported (11,15,19), but the experiments were typically performed in shake-flask cultures with product yields of 10 to 30 mg/liter. Plasmid-based gene expression under high-cell-density cultivation may dramatically promote problems related to plasmid instability and lysis of recombinant cells (16,28).…”
mentioning
confidence: 99%
“…The Pel B leader sequence in the expression plasmid facilitated the transportation of the scFv into the oxidizing environment of the E. coli periplasmic space, a space where two intra-domain disulfide bonds in the scFv can take place. (52) However, previous findings have indicated that the presence of unpaired cysteine at the C-terminus affects the yield of soluble scFv production by forming covalent aggregates with other proteins containing cysteine within the periplasmic space. (10,32) To overcome this obstacle, the conditions for hscFv-C production were investigated.…”
Section: Discussionmentioning
confidence: 99%